Pelatihan Pengolahan Sampah Organik Rumah Tangga Menjadi Eco-Enzyme di Desa Tenjoayu - Septi Kurniasih; Muhammad Agus Hardiansyah; Lukman Nulhakim (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
Organic waste is waste generated from the use of organic materials in various daily lives. The absence of a disposal site and waste management system results in organic waste not being processed properly, resulting in environmental problems in the form of pollution and unpleasant odors in the area of Tenjo Ayu Village. Most household waste is organic waste, such as vegetable residue, fruit peels and yard sweepings. The service activity of the workshop on processing organic waste into eco-enzyme aims to educate the public regarding the processing of household waste into eco-enzyme as a multifunctional liquid so that waste can be reused into cleaning products and organic fertilizers that have economic value. This community service activity has succeeded in providing insight and skills to the community regarding the processing of organic waste into eco-enzymes.